PEMBUATAN APLIKASI E-COMMERCE BERBASIS WEBSITE PADA PT WSW GRUP INDONESIA - Adrian Santoso; Tony Tony (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
The purpose of this thesis is to design information systems sales aroma diffuser that can assist the sales department in view of the sales and allow companies to sell his goods. System design method used is the system development life cycle (SDLC). application development is done by using a programming language hypertext preprocessor (PHP) with the database using MYSQL.